Light-controlled disruption of cancer cell dormancy via photoswitchable stress hormone receptor degraders - Karina M. Freitag; Robin Scheuplein; Chiara Orlacchio; Viola Ansuinelli; Tommaso Fava; Vincent Fischer; Bohan Zhang; Miriam Kretschmer; Mahshid Gazorpak; Erick M. Carreira; Katharina Gapp (Proceedings of the National Academy of Sciences, 2026)
Cancer cell dormancy is a key contributor to therapy resistance and disease relapse. The glucocorticoid receptor (GR), a major mediator of stress hormone signaling, has emerged as a central regulator of dormancy in non-lymphoid solid tumors, particularly lung cancer. However, systemic GR inhibition or degradation using conventional Proteolysis Targeting Chimeras (PROTACs) risks widespread on-target toxicity due to their constitutive activity. We hypothesized that integrating photoswitchable elements into PROTACs, termed photoPROTACs, would enable wavelength-specific, spatiotemporally precise modulation of GR degradation and dormancy-associated signaling pathways. Here, we synthesized a diverse series of photoPROTACs incorporating photoswitchable arylazotriazole or arylazopyrazole scaffolds, including previously unreported (OEt) 2 - and (NMe 2 ) 2 -substituted photoswitches. Arylazopyrazole-based GR photoPROTACs bearing Me 2 - and (OEt) 2 substituents exhibited near-quantitative photoisomerization (95% Z- isomer; 89 to 92% E- isomer), no photobleaching, and thermal half-lives in the range of 3 to 12.2 d in dimethyl sulfoxide (DMSO). Among them, KH-5-306 and KH-5-309 induced potent, specific, and reversible GR degradation in their thermodynamically stable E- isomeric form at low nanomolar concentrations, with markedly reduced activity in the Z- isomeric state. Transcriptomic profiling showed that E- KH-5-309 disrupts GR-driven dormancy-associated gene expression programs in a non–small cell lung cancer (NSCLC) model, while the Z- isomer remains functionally inert. Our findings establish a framework for the rational design of photoswitchable PROTACs beyond GR and demonstrate their potential to achieve spatiotemporal control of stress hormone receptor signaling, enabling mechanistic insights into GR function and the targeted disruption of cancer cell dormancy.